Relating off‐premises alcohol outlet density to intentional and unintentional injuries. (9th October 2015) - Morrison, Christopher; Smith, Karen; Gruenewald, Paul J.; Ponicki, William R.; Lee, Juliet P.; Cameron, Peter
Abstract: Aims: This study investigated the hypotheses that (i) intentional and unintentional injuries occur more frequently in areas with greater density of off‐premises alcohol outlets; and (ii) larger and chain outlets selling cheaper alcohol contribute more substantially to injury risk than smaller and independent outlets. Design: Ecological cross‐sectional. Setting: From the 256 Statistical Area level 2 (SA2) census units in Melbourne, Australia, we selected a random sample of 62 units. There were 2119 Statistical Area level 1 (SA1) units nested within the selected SA2 units. Participants: The selected units contained 295 off‐premises outlets. Measurements: Two independent observers conducted premises assessments in all off‐premises outlets, assessing the volume of alcohol available for sale (paces of shelf space), price (least wine price) and other operating characteristics (chain versus independent, drive‐through). Outlet counts, assessed outlet characteristics and other area characteristics (population density, median age, median income, retail zoning) were aggregated within SA1 units. Dependent variables were counts of ambulance attended intentional injuries (assaults, stabbings, shootings) and unintentional injuries (falls, crush injuries and object strikes). Findings: In univariable analyses, chain outlets were larger ( r = 0.383; P < 0.001) and sold cheaper alcohol ( r = −0.484; P < 0.001) compared with independent outlets. In Bayesian spatial Poisson models, off‐premises outlet density was positively related to both intentional [incidence rate ratio (IRR) = 1.38; 95% credible interval (CI) = 1.19, 1.60] and unintentional injuries (IRR = 1.18; 95% CI = 1.06, 1.30). After disaggregation by outlet characteristics, chain outlet density was also related to both intentional (IRR = 1.35; 95% CI = 1.11, 1.64) and unintentional injuries (IRR = 1.20; 95% CI = 1.08, 1.38). Conclusions: Greater off‐premises outlet density is related to greater incidence of traumatic injury, and chain outlets appear to contribute most substantially to traumatic injury risk.